Perioperative glycemia regulation for insulinoma surgery – challenges faced by the anaesthesiologist. A case report. - Mihalek, Nora; Starcevic, Sanja; Erdoes, Gabor; Radovanovic, Dragana (Archive of Oncology, 2025)
Insulinoma represents a benign, insulin-secreting neuroendocrine tumor of the beta cells of islets of Langerhans in the pancreas, which leads to frequent episodes of hypoglycemia. Surgery is the definite treatment. However, the perioperative treatment of patients with insulinoma is highly challenging. We present the perioperative management of a 46-year-old obese male patient with insulinoma. As the patient reported frequent severe hypoglycemia episodes, the main priority of the perioperative treatment was to prevent hypoglycemia before tumor resection and to control rebound hyperglycemia after tumor removal. Maintaining normoglycemia was challenging during the regular fasting period before abdominal surgery, as well as during the intervention, as general anaesthesia masks the symptoms of hypoglycemia. Obesity further complicated the anaesthetic management, due to expected difficult airway management and central venous access. Glycemia was monitored in 15-minute intervals during surgery and in 30-minute intervals postoperatively, and dysglycemia was corrected according to the trend of variations. As insulinoma is a rare phenomenon with an unpredictable clinical course, current reportings regarding the anaesthetic management of patients with this pathology are relatively lacking. Therefore, our case report could contribute to expanding the limited data about the perioperative treatment of patients with this condition.